تحليل الصراعات الدولية المعاصرة : بين الأبعاد الثقافية والاعتبارات الاستراتيجية - نور الدين، فوزي Nouruldin, Fawzi (جامعة محمد خيضر بسكرة, 2014)
تمثل ظاهرة الصراع الجانب الأكثر بروزا وحركية في السياسة الدولية المعاصرة. وقد كان للتحولات الجذرية التي أعقبت نهاية الحرب الباردة انعكاسات بالغة الأهمية على طبيعة ومضمون الصراعات الدولية، خصوصا بعد تراجع العوامل العسكرية والإيديولوجية وتصاعد العوامل الاقتصادية والثقافية في العلاقات الدولية. تحاول الدراسة استكشاف وتحليل مضمون النظريات التي حاولت تفسير طبيعة الصراعات الدولية منذ نهاية الحرب الباردة. تخلص الدراسة، انه بالرغم من الأهمية النسبية لدور العوامل الثقافية كمحرك للصراعات الدولية المعاصرة، إلا أن الاعتبارات الاستراتيجية المرتبطة بالقوة والمصالح القومية تبقى حاضرة بقوة في معظم الصراعات، ويتم اللجوء إلى الاعتبارات الثقافية في كثير من الأحيان للتغطية على سياسات القوة السائدة في عالمنا المعاصر. The conflict phenomenon represents the part which is the more apparent and active in contemporary international policy. The radical change that occurred after the Cold War affected considerably the nature and the content of the international conflicts, especially after the retreat of military and ideological factors, and the rising of the economic and cultural role in international relations. The study tries to discover and analyses the content of the theories that try to explain the nature of international conflicts since the end of the Cold War. As a result, regardless of the relative importance of the cultural factors as a motif for a contemporary international conflicts, while the strategic considerations that have a relation with power and national interests remains present in these conflicts. Thus, there is a resort to cultural considerations in order to hide the policies of power that are dominant in our contemporary world.
Keywords: السياسة الدولية -- الصراع الدولي -- صراع الحضارات -- العولمة الثقافية